1998
DOI: 10.1016/s0029-7844(97)00590-5
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of Clinical and Sonographic Estimates of Birth Weight: Experience With 1034 Parturients

Abstract: The apparent superiority of sonographic EFW over clinical EFW applies principally to preterm pregnancies. The prediction limitation calculation suggests that either method, for any particular estimate between 500 and 4500 g, has limited value in the estimation of actual birth weight, because this outcome is highly variable and frequently lies outside of the useful bandwidth (+/- 10%) for prospective management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
109
6
6

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(133 citation statements)
references
References 13 publications
12
109
6
6
Order By: Relevance
“…Previous papers have indicated that the inter and intraobserver variability of uterine height measurements is small, ranging from 0.52 cm to 1.72 cm. 12 In the largest study evaluating the accuracy of FWE through clinical palpation (n = 661 full-term patients), Chauhan et al 13 reported a mean absolute weight error of 367 g and a mean absolute percentage error of 10.3, which are very similar to the numbers obtained using Johnson's formula in the present study. Assuming that the accuracy of FWE using Leopold's maneuvers and Johnson's method is similar, it seems that since Johnson's method relies on objective measurements and calculations, this latter method of FWE may be easier to perform and teach, especially to midwives or less experienced examiners such as medical students or residents.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous papers have indicated that the inter and intraobserver variability of uterine height measurements is small, ranging from 0.52 cm to 1.72 cm. 12 In the largest study evaluating the accuracy of FWE through clinical palpation (n = 661 full-term patients), Chauhan et al 13 reported a mean absolute weight error of 367 g and a mean absolute percentage error of 10.3, which are very similar to the numbers obtained using Johnson's formula in the present study. Assuming that the accuracy of FWE using Leopold's maneuvers and Johnson's method is similar, it seems that since Johnson's method relies on objective measurements and calculations, this latter method of FWE may be easier to perform and teach, especially to midwives or less experienced examiners such as medical students or residents.…”
Section: Discussionsupporting
confidence: 86%
“…18 While some studies have indicated that ultrasound FWE is superior 19,20 or inferior 2,21 to clinical predictions, most have reported that the two methods have similar accuracy. 1,4,8,17,22 In the largest study comparing ultrasound versus clinical FWE, Chauhan et al 13 did not find significant differences in 460 patients at gestational ages of between 37 and 40 weeks. While clinical estimates were correct (± 10%) in 61.7% of their cases, ultrasound estimates were correct in 60%.…”
Section: Discussionmentioning
confidence: 97%
“…In our series, a fetal weight greater than 4300 g was significantly associated with a risk of caesarean delivery, which differs from the recommendations of the High Authority of Health [11] and the American College of Obstetrics and Gynecologists [12]. Indeed, the latter recommend to perform a Caesarean section programmed in the case of weight estimate greater than or equal to 5000 g in the absence of diabetes or 4500 g in the case of diabetes (Table 4).…”
Section: Discussioncontrasting
confidence: 71%
“…For instance, management of diabetic pregnancy, vaginal birth after a previous caesarean section, and intrapartum management of fetuses presenting by the breech will be greatly influenced by estimated fetal weight. 8,9 During the initial era or before the birth of science fetal weight estimation was more a kind guess work. The cardinal importance of knowledge of the size and shape of the fetal head in order to understand the mechanism of labor was first recognized by Smellie (1752) who also pointed out that it is the biparietal diameter which passes through the narrowest part of the pelvic brim.…”
Section: Introductionmentioning
confidence: 99%